"Governance for Sustainability" und die Zone der Wissenstransaktionen. Wissen und Steuerung am Beispiel der lokalen Umsetzung von europäischen Feinstaubregulierungen. - Matthiesen, Ulf; Reisinger, Eva (TH Zürich, NSL, 2009)
Der Beitrag widmet sich einem konkreten Mehr-Ebenen-Governance-Fall, der insbesondere für die Stadtplanung und lokale Verwaltungen erhebliche Herausforderungen bereithält: der Umsetzung der europäischen Feinstaubregulierungen 1996/92/EC und 1999/30/EC. Mit dem KnowledgeScapes-Ansatz als heuristischem Konzept sowie einer besonderen Fokussierung auf neue Transaktionszonen des Wissens untersucht der Essay am konkreten Fall der Landeshauptstadt Potsdam die Implementierungsversuche einer zentralen europäischen Regulierungsvorschrift und damit auch die Umsetzung nachhaltiger Umweltpolitikziele auf diesem Feld.

The integration and intertwinement of knowledge and politics have entered a new level due to the complex and dynamic developments in our current knowledge-based society. New transaction zones can be detected where especially knowledge of experts and scientists have gained a decisive role. At the same time, scientific expert knowledge integrates not always other relevant knowledge forms in productive manners. Based on this observation, the paper discusses insights from a study on the implementation of the recent European Air Quality Framework Directive (96/92/EC) on the issue of particulate matter (PM10) in the City of Potsdam. In this specific case city, officials were obliged to introduce a novel policy of local air quality management and assessment - induced by a knowledge-driven, externally imposed meta governance. In distinguishing different knowledge forms our study reveals the increasing dominance of scientific and expert knowledge in hierarchical governance arrangements and demonstrates how this increase translates into politics. Steering and institutional knowledge became essential when the policy initiative moved through administration and government, showing the transcoding into relevant knowledge. Experience-based knowledge of the life world domain, i.e. of citizens, was less successful in entering the action arena. In sum, although only minor governance innovations are detected, the case pursues new forms and alterations in the relation of knowledge and politics.
Governance for sustainability and the zone of knowledge transaction - knowledge and control: An example of local implementation of European fine particle regulations.
Keywords: Umweltschutz; Umweltpolitik; Wissenschaft; Luftreinhaltung; Schadstoff; Grenzwert; Immissionsschutz; Feinstaub; Governance; EU-Richtlinie; Umsetzung; Wissen; Expertenwissen; Luftreinhaltepolitik; Luftschadstoff; Schadstoffkonzentration